PERSEPSI PEMILIH PEMULA SISWA MA AL ASROR TERHADAP PARTAI POLITIK ISLAM TAHUN 2014 - Anglia, Erna (Civic Education Program, Universitas Negeri Semarang, 2017)
This research is to know about first participant perception of students at MA Al Asror to Islam politics party 2014 and what influence factors that perception. Quantitative and qualitative methods is use by this research. The location is MA Al Asror at Jl. Legoksari Raya No 02 Patemon Kecamatan Gunungpati Kabupaten Semarang. The population are 138 students MA Al Asror 2014/2015 of 12nd class, and 101 students as respondent. Primary and secondary data is data source. The questionnaires and interview as collecting data technique. Data analysis method used is descriptive percentage analysis. The result showed that first participant perception of students at MA Al Asror to Islam politics party 2014 on good criteria (84,55%). The influence factors of this perception is want to looking for information and participate the politics activity, perspective and mission, work programs, and family’s area.